2022
DOI: 10.1039/d1cy02112e
|View full text |Cite
|
Sign up to set email alerts
|

Crystal phase-selective synthesis of intermetallic palladium borides and their phase-regulated (electro)catalytic properties

Abstract: Three crystal phases of Pd-B intermetallics, including Pd6B, Pd5B2 and Pd2B, are synthesized, and their phase-dependent catalytic activities toward electrochemical water splitting and Suzuki coupling reaction are studied. In both...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Similar d-band regulations through changing B contents were also This journal is © The Royal Society of Chemistry 2022 verified in the other intermetallic boride systems (e.g., W-B, Mo-B, and Pd-B). 79,81,82 In addition to the contents, the distribution and order of interstitial B atoms largely affect the d-band properties of transition metals. Our research group used Pd-B as a model to investigate the influence of these factors in detail.…”
Section: Intermetallic Catalystsmentioning
confidence: 99%
“…Similar d-band regulations through changing B contents were also This journal is © The Royal Society of Chemistry 2022 verified in the other intermetallic boride systems (e.g., W-B, Mo-B, and Pd-B). 79,81,82 In addition to the contents, the distribution and order of interstitial B atoms largely affect the d-band properties of transition metals. Our research group used Pd-B as a model to investigate the influence of these factors in detail.…”
Section: Intermetallic Catalystsmentioning
confidence: 99%
“…Li et al synthesized Pd 2 B intermetallic compound via solid phase reactions, which was applied to catalyze the Suzuki coupling reaction. 1136 After reacting for 16 h, Pd 2 B exhibited a high conversion of 89%, while the Pd counterpart generated the desired product only at a rate of 50%. The theoretical and experimental studies showed that an increase in B content in the Pd lattice can cause a downshift in the d-band center and improve the surface adsorption properties.…”
Section: Catalysismentioning
confidence: 98%
“…Li et al . synthesized Pd 2 B intermetallic compound via solid phase reactions, which was applied to catalyze the Suzuki coupling reaction . After reacting for 16 h, Pd 2 B exhibited a high conversion of 89%, while the Pd counterpart generated the desired product only at a rate of 50%.…”
Section: Potential Applications Of Unconventional-phase Nanomaterialsmentioning
confidence: 99%
“…Transition metal diborides have emerged as promising electrocatalysts theoretically due to the strong hybridization between d orbitals of the transition metal and sp orbitals of boron. [340][341][342] Metal borides also show resistance against alkaline corrosion as an eletrocatalyst. 343 Yin et al synthesized TiB 2 by selfpropagating high-temperature synthesis as the support for Pt loading by the Nafion film in ORR.…”
Section: Metal Boridesmentioning
confidence: 99%